Some Account of the Design of the Trustees for Establishing Colonys in America - McIlvenna, Noeleen (Georgia Open History Library, 1990)
Some Account of the Design of the Trustees for Establishing Colonys in America is a pamphlet authored by James Edward Oglethorpe, founder of the colony of Georgia. In this pamphlet, Oglethorpe ventures into American colonial theory, explores ideas about the southern frontier, and clears a path for the success of his new colony of Georgia. Oglethorpe grapples with questions related to settlement, such as the relationship between the established Church and the individual settler or the type of site he wanted for his colony. Some Account of the Design of the Trustees for Establishing Colonys in America offers new insight into the early days of the colony of Georgia and its founder. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.